Physicochemical Properties and Bioreactivity of Sub‐10 μm Geogenic Particles: Comparison of Volcanic Ash and Desert Dust - Ines Tomašek; Julia Eychenne; David E. Damby; Adrian J. Hornby; Manolis N. Romanias; Severine Moune; Gaëlle Uzu; Federica Schiavi; Maeva Dole; Emmanuel Gardès; Mickael Laumonier; Clara Gorce; et al. (GeoHealth)
Abstract Exposure to ambient particulate matter (PM) with an aerodynamic diameter of <10 μm (PM10) is a well‐established health hazard. There is increasing evidence that geogenic (Earth‐derived) particles can induce adverse biological effects upon inhalation, though there is high variability in particle bioreactivity that is associated with particle source and physicochemical properties. In this study, we investigated physicochemical properties and biological reactivity of volcanic ash from the April 2021 eruption of La Soufrière volcano, St. Vincent, and two desert dust samples: a standardized test dust from Arizona and an aeolian Gobi Desert dust sampled in China. We determined particle size, morphology, mineralogy, surface texture and chemistry in sub‐10 μm material to investigate associations between particle physicochemical properties and observed bioreactivity. We assessed cellular responses (cytotoxic and pro‐inflammatory effects) to acute particle exposures (24 hr) in monocultures at the air‐liquid interface using two types of cells of the human airways: BEAS‐2B bronchial epithelial cells and A549 alveolar type II epithelial cells. In acellular assays, we also assessed particle oxidative potential and the presence of microorganisms. The results showed that volcanic ash and desert dust exhibit intrinsically different particle morphology, surface textures and chemistry, and variable mineralogical content. We found that Gobi Desert dust is more bioreactive than freshly erupted volcanic ash and Arizona test dust, which is possibly linked to the presence of microorganisms (bacteria) and/or nanoscale elongated silicate minerals (potentially clay such as illite or vermiculite) on particle surfaces.